Novel cationic trypsinogen (PRSS1) N29T and R122C mutations cause autosomal dominant hereditary pancreatitis. Issue 2 (1st February 2002) - Pfützer, R; Myers, E; Applebaum-Shapiro, S; Finch, R; Ellis, I; Neoptolemos, J; Kant, J A; Whitcomb, D C
Abstract : Hereditary pancreatitis (HP) is usually caused by mutations in the cationic trypsinogen (PRSS1) gene, especially R122H or N29I. We sequenced the PRSS1 gene in the proband of families without these common mutations. Novel R122C and N29T mutations were detected in independent families that segregated with the disease in an autosomal dominant fashion. The R122C mutation eliminates the arginine autolysis site as with R122H mutations. The N29T mutation may also enhance intrapancreatic trypsin activity as has been demonstrated in vitro. Identification of these new mutations requires special attention as commonly used detection methods may fail.